Case report: Acute necrotizing encephalopathy: a report of a favorable outcome and systematic meta-analysis of outcomes with different immunosuppressive therapies - Fischell, Stefanie Zaner; Fischell, Jonathan; Kliot, Tamara; Tumulty, Jamie; Thompson, Stephen J.; Raees, Madiha Q. (Frontiers in Neurology, 2023)
Acute Necrotizing Encephalopathy (ANE) is a condition characterized by symmetric, bilateral lesions affecting the thalamus and potentially other areas of the brain following an acute febrile illness. It manifests clinically as abrupt development of encephalopathy, or alteration in mental status that often includes development of seizures and progression to coma. Treatment strategies combine immunosuppressive therapies and supportive care with varying levels of recovery, however there are no universally accepted, data-driven, treatment algorithms for ANE. We first report a case of a previously healthy 10-year-old female with acute onset diplopia, visual hallucinations, lethargy, and seizures in the setting of subacute non-specific viral symptoms and found to have bilateral thalamic and brainstem lesions on MRI consistent with ANE. She was treated with a combination of immunomodulatory therapies and ultimately had a good outcome. Next, we present a meta-analysis of 10 articles with a total of 158 patients meeting clinical and radiographic criteria for ANE. Each article reported immunosuppressive treatments received, and associated morbidity or mortality outcome for each individual patient. Through our analysis, we confirm the effectiveness of high-dose, intravenous, methylprednisolone (HD-IV-MP) therapy implemented early in the disease course (initiation within 24 hours of neurologic symptom onset). There was no significant difference between patients treated with and without intravenous immunoglobulin (IVIG). There was no benefit of combining IVIG with early HD-IV-MP. There is weak evidence suggesting a benefit of IL-6 inhibitor tocilizumab, especially when used in combination with early HD-IV-MP, though this analysis was limited by sample size. Finally, plasma exchange (PLEX) improved survival. We hope this meta-analysis will be useful for clinicians making treatment decisions for patients with this potentially devastating condition.